2009
DOI: 10.1099/ijs.0.000620-0
|View full text |Cite
|
Sign up to set email alerts
|

Carboxydothermus siderophilus sp. nov., a thermophilic, hydrogenogenic, carboxydotrophic, dissimilatory Fe(III)-reducing bacterium from a Kamchatka hot spring

Abstract: Carboxydothermus siderophilus sp. nov., a thermophilic, hydrogenogenic, carboxydotrophic, dissimilatory Fe(III)-reducing bacterium from a Kamchatka hot spring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…At the time of writing, the genus Carboxydothermus contains three species with validly published names: C. hydrogenoformans (Svetlichny et al, 1991), C. ferrireducens (Slobodkin et al, 2006) and C. siderophilus (Slepova et al, 2009). Strain R1 T 5DSM 7242 T , initially described as 'Carboxydothermus restrictus' (Svetlichny et al, 1994), was later shown to belong to a different phylogenetic lineage and was reclassified as Thermolithobacter carboxydivorans (Sokolova et al, 2007).…”
mentioning
confidence: 99%
“…At the time of writing, the genus Carboxydothermus contains three species with validly published names: C. hydrogenoformans (Svetlichny et al, 1991), C. ferrireducens (Slobodkin et al, 2006) and C. siderophilus (Slepova et al, 2009). Strain R1 T 5DSM 7242 T , initially described as 'Carboxydothermus restrictus' (Svetlichny et al, 1994), was later shown to belong to a different phylogenetic lineage and was reclassified as Thermolithobacter carboxydivorans (Sokolova et al, 2007).…”
mentioning
confidence: 99%
“…Recent studies have shown physiological diversity in situations where hydrogenogenic growth can also occur simultaneously with the reduction of various electron acceptors (reviewed by Oelgeschläger & Rother, 2008;Sokolova et al, 2009). For example, ferric iron is reduced by Carboxydothermus siderophilus (Slepova et al, 2009) and Thermosinus carboxydivorans (Sokolova et al, 2004b), and elemental sulfur is reduced by some strains of the archaeal genus Thermococcus (Sokolova et al, 2004a;Lee et al, 2008). At present, there are no reports on carboxydotrophic bacteria isolated from acidic hydrothermal environments that are usually rich in ferric iron and elemental sulfur (Stetter, 2005).…”
mentioning
confidence: 99%
“…Strains: 1, Ug1 T ; 2, C. hydrogenoformans Z-2901 T ; 3, C. ferrireducens JW/AS-Y7 T ; 4, C. siderophilus 1315 T ; and 5, C. islandicus SET IS-9 T . Data for reference strains are taken from Svetlichny et al (1991), Henstra & Stams (2004), Slobodkin et al (1997Slobodkin et al ( , 2006, Slepova et al (2009) …”
mentioning
confidence: 99%
“…Essential genes and reactions in the EFM pathways could not be deleted [43]. For the model of acetyl-CoA pathway, elementary mode (EM) has been systematically used to examine gene deletion that influence the hydrogen yield of C. hydrogenoformans as well as to identify a set of multiple gene knockout which results in higher product yield.…”
Section: Resultsmentioning
confidence: 99%